A risk‐adapted approach to treating respiratory syncytial virus and human parainfluenza virus in allogeneic stem cell transplantation recipients with oral ribavirin therapy: A pilot study. Issue 4 (17th July 2017) - Piñana, José Luis; Hernández‐Boluda, Juan Carlos; Calabuig, Marisa; Ballester, Isabel; Marín, Manuela; Madrid, Silvia; Teruel, Anabel; Terol, María‐José; Navarro, David; Solano, Carlos
Abstract: Here we report the applicability of a protocol based on clinical conditions and risk factors (RFs) for managing 35 allogeneic hematopoietic stem cell transplantation (allo‐HSCT) recipients who developed a total of 52 episodes of respiratory viral infections (RVIs) caused by respiratory syncytial virus (RSV; n=19), human parainfluenza virus (HPIV; n=29), or both (n=4) over a 2‐year study period. Risk categories were classified as high risk (cat‐1) when the immunodeficiency scoring index was ≥3 and/or ≥3 RFs and/or ≥1 co‐infective virus(es) were present; the remaining cases were classified as low risk (cat‐0). The presence of two or more signs or symptoms including fever (T>38 °C), sinusitis, otitis, sore throat, tonsillitis, or baseline C‐reactive protein increased by >2‐fold at the time of the RVI, was considered a clinically‐intense episode (CIE). Overall, 34 out of 52 episodes (65%) were limited to upper respiratory tract infections (URTIs). Overall, 26 (50%) received oral ribavirin. Twenty‐four of 40 (60%) cat‐1 episodes were treated, compared to 2 of 12 (17%) cat‐0 RVIs ( P =.01), while 17 of the 25 (68%) CIEs were treated compared to 9 of the remaining 27 (33%) episodes ( P =.02). Regardless of antiviral therapy, the overall resolution rate was 100% for URTI and 95% for lower respiratory tract infection; the virus‐related mortality was low (4%). In conclusion, the use of a risk‐adapted protocol to guide therapeutic decisions for allo‐HSCT recipients with RSV or HPIV RVIs is feasible and may limit unnecessary antiviral therapy.